The impact of reduced red and processed meat consumption on cardiovascular risk factors; an intervention trial in healthy volunteers. Issue 10 (27th September 2019) - Simpson, Elizabeth J.; Clark, Marie; Razak, Azlina A.; Salter, Andrew
Abstract : Reductions in red meat intake lowered LDL in men, but may have unfavourable short term impact on blood cell numbers. Abstract : Meat represents an important part of the diet for many adults, supplying essential amino acids and micronutrients. However, high red and processed meat (RPM) intake is implicated in the development of cardiovascular disease and dyslipidemia. This study aimed to reduce RPM consumption in healthy, non-obese omnivores (21–48 years), who ate RPM ≥4 times per week, and to investigate its effect on cardiovascular risk factors using a single-group longitudinal study design (comprising an initial 4-week baseline period, followed by a 12-week intervention). Participants (16M : 21F) were assessed before (BL) and after (T0) the pre-intervention period and before (T0), at week 6 (T6) and at the end of intervention (T12). In a subset (8M : 15F), haematological parameters were measured at BL, T6 and T12. Compared with BL, protein intake from RPM reduced by 67% at T6 and 47% at T12 (4-day dietary records). BMI, body fat mass, and blood pressure did not change over the intervention in the whole cohort, but mean total, LDL and HDL cholesterol were reduced in males at T12 (effect sizes −0.52, −0.41 and −0.15 mmol l −1, respectively; each P < 0.01), with no change in total : HDL ratio observed. In the study sub-set, haemoglobin concentration, plus red and white cell count fell during the intervention (estimated effect size ηp 2 0.300, 0.301 and 0.354, respectively; each P < 0.001). It was possible for omnivores to approximately halve their RPM intake, and in males this dietary change appeared to reduce blood lipid concentrations. However, acute dietary changes to RPM intake may have had an unfavourable impact on haematological parameters.